2014
DOI: 10.1002/pa.1518
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of provincial governments in China from 2001 to 2010: measurement and analysis

Abstract: Measurement and analysis of local government efficiency is important; however, it is also difficult. To measure government efficiency, this paper employs the relative measurement method described in the research literature. It develops and applies an index to measure and rank the government efficiency of 31 provincial governments in China (including autonomous regions and municipalities) from 2001 to 2010. This permits a comparative analysis of provincial government efficiency and of the factors that influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
(9 reference statements)
2
17
0
Order By: Relevance
“…Low government efficiency is also in evidence further inland in Sichuan, Ningxia, and Gansu provinces (Figure ). This geographical distribution of urban government efficiency mirrors that proposed by R. Tang et al () at provincial level.…”
Section: Urban Growth In China: Some Stylized Factssupporting
confidence: 86%
See 2 more Smart Citations
“…Low government efficiency is also in evidence further inland in Sichuan, Ningxia, and Gansu provinces (Figure ). This geographical distribution of urban government efficiency mirrors that proposed by R. Tang et al () at provincial level.…”
Section: Urban Growth In China: Some Stylized Factssupporting
confidence: 86%
“…They showed that high levels of government efficiency and efforts to fight corruption drew considerable amounts of FDI to the provinces that had made the biggest strides in this respect. R. Tang, Tang, and Lee (, p. 151) pointed that government efficiency at provincial level was “an important factor in strengthening the regional economy,” although they considered the direction of causality problematic.…”
Section: Understanding Urban Growth In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…These dynamics of industrial and political interests might help or hinder transformations to sustainability. Hence, there is an urgent need for innovation in political achievement evaluation and governance decision-making systems in order to set adaptive policies and catalyse urban sustainability transitions (Roseland and Connelly, 2005;Tang et al, 2014). The government is expected to make efforts to proactively identify urban transition points, set realistic goals, promote economic transformation and diversification, assign responsibilities, and facilitate strategy implementation sequentially.…”
Section: Innovation In Governance and Decision-making Systemmentioning
confidence: 99%
“…Governmental efficiency can affect firm productivity, and transaction cost of trade. Tang et al (2014). The index is calculated on the basis of four main indicators, namely government public service, public infrastructure, governmental size and residents' economic welfare, which are subdivided into further categories.…”
Section: Introductionmentioning
confidence: 99%